2023
DOI: 10.5194/egusphere-2023-166
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multi-decadal past winter temperature, precipitation and snow cover information over the European Alps using multiple datasets

Abstract: Abstract. Assessing past distributions, variability and trends of the mountain snow cover and its first order drivers, temperature and precipitation, is key for a wide range of studies and applications. In this study, we compare the results of various modelling systems (global and regional reanalyses ERA5, ERA5-Land, ERA5-Crocus, CERRA-Land, UERRA MESCAN-SURFEX, MTMSI, and regional climate model simulations CNRM-ALADIN and CNRM-AROME driven by the global reanalysis ERA-Interim) against observational references… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 64 publications
(91 reference statements)
0
3
0
Order By: Relevance
“…Although no data assimilation was used in ERA5-Land, the atmospheric forcings were directly constrained by assimilated observations (Räisänen, 2021). However, ERA5-Land has been found to show especially large overestimation of SWE in the European Alps (Monteiro & Morin, 2023). On the other hand, Lei et al (2022) found snow depth of ERA5-Land represents snow absence well and compares reasonably well with in situ observations of snow depth over the Tibetan Plateau.…”
Section: Discrepancies In Snow Drought Between Models and Era5mentioning
confidence: 69%
See 1 more Smart Citation
“…Although no data assimilation was used in ERA5-Land, the atmospheric forcings were directly constrained by assimilated observations (Räisänen, 2021). However, ERA5-Land has been found to show especially large overestimation of SWE in the European Alps (Monteiro & Morin, 2023). On the other hand, Lei et al (2022) found snow depth of ERA5-Land represents snow absence well and compares reasonably well with in situ observations of snow depth over the Tibetan Plateau.…”
Section: Discrepancies In Snow Drought Between Models and Era5mentioning
confidence: 69%
“…Although no data assimilation was used in ERA5‐Land, the atmospheric forcings were directly constrained by assimilated observations (Räisänen, 2021). However, ERA5‐Land has been found to show especially large overestimation of SWE in the European Alps (Monteiro & Morin, 2023). On the other hand, Lei et al.…”
Section: Discussionmentioning
confidence: 99%
“…First, land surface meteorological variables are notoriously difficult to model at high elevation because of the scarcity of available observations and the importance of processes that depend on topography and that are not accounted for by climate re-analyses (Vionnet et al, 2019). The ERA5-land products have proven useful for capturing the main features of surface variable trends in the European Alps (Monteiro and Morin, 2023), and have outcompeted other climate gridded products, such as E-OBS, in areas where the density of weather stations is low (Bandhauer et al, 2022), as is the case in the southwestern Alps. However, its coarse spatial resolution limits its usefulness for representing local heterogeneity in bioclimatic conditions on the ground.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there are studies evaluating regional climate models based on multi-decadal simulations, but these are at coarser spatial resolution (Daloz et al, 2022: 0.11°;Matiu and Hanzer, 2022: 0.11°;Steger et al, 2013: 0.22°). Recently, Monteiro and Morin (2023) compared the performance of multiple model systems with spatial resolutions ranging from 2.5 to 30 km over the European Alps. They found that main features of the snow cover, snow depth, and driving climatic conditions could be reproduced by the models but with increasing deviations at higher altitude.…”
Section: Introductionmentioning
confidence: 99%
“…Climate change already affects and will further alter snow dynamics and conditions (Dong and Menzel, 2020;Monteiro and Morin, 2023), which is why observation-based analyses are limited. Climate impact research and data users benefit from information at the local scale (Orr et al, 2021).…”
Section: Introductionmentioning
confidence: 99%